2017
DOI: 10.3390/ijms18020131
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycoprofiling Analysis for Carbohydrate Composition and Site-Occupancy Determination in a Poly-Glycosylated Protein: Human Thyrotropin of Different Origins

Abstract: Human thyrotropin (hTSH) is a glycoprotein with three potential glycosylation sites: two in the α-subunit and one in the β-subunit. These sites are not always occupied and occupancy is frequently neglected in glycoprotein characterization, even though it is related to folding, trafficking, initiation of inflammation and host defense, as well as congenital disorders of glycosylation (CDG). For the first time N-glycoprofiling analysis was applied to the site-occupancy determination of two native pituitary hTSH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
1
4
0
2
Order By: Relevance
“…From Table 1 we can also confirm that the percentage of sialylated glycans (11.4%) even being quite higher than it was for pit-G-hPRL (1.7%) or even for HEK-hTSH (4.7%) (Sant’Ana et al 2018), still is much lower when compared to that found in CHO-derived G-hPRL (80.5%). The percentage of fucosylated glycans was found quite high in native and recombinant G-hPRL (> 60%), especially in comparison with native and CHO-derived hTSH, whose percent of fucosylated glycans was 35.2 and 11.9 respectively (Ribela et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From Table 1 we can also confirm that the percentage of sialylated glycans (11.4%) even being quite higher than it was for pit-G-hPRL (1.7%) or even for HEK-hTSH (4.7%) (Sant’Ana et al 2018), still is much lower when compared to that found in CHO-derived G-hPRL (80.5%). The percentage of fucosylated glycans was found quite high in native and recombinant G-hPRL (> 60%), especially in comparison with native and CHO-derived hTSH, whose percent of fucosylated glycans was 35.2 and 11.9 respectively (Ribela et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The main goal of our study, however, was the analysis of the N-glycan structures present in HEK-G-hPRL, considering that in previous work we already compared in this respect, pituitary-derived G-hPRL with CHO-derived G-hPRL (Capone et al 2015), pituitary-derived hTSH with CHO-derived hTSH (Ribela et al 2017) and these same products with HEK-derived hTSH (Sant’Ana et al 2018). We soon observed that human cells, either from native or from embryonic kidney cells, produced a much higher number of different N-glycan structures (n = 28), while CHO cells only produced 14, a number practically matching with that obtained analyzing CHO-hTSH (n = 15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O processo de glicosilação de proteínas é um dos mais importantes e o mais comum entre as possíveis modificações pós-traducionais, sendo responsável por uma variedade de funções celulares e também distúrbios fisiológicos referentes à deficiência na glicosilação de proteínas (PETRESCU et al, 2004;BARONE et al, 2008;TIAN e ZHANG, 2010;FOGLI et al, 2012;LOSFELD et al, 2012;PAN et al, 2012). Comumente, esse processo ocorre por meio da transferência de uma cadeia oligossacarídica à proteína, contudo, a ocupação do sítio de glicosilação determinará a sua atividade biológica (THOTAKURA et al, 1991;SZKUDLINSKI et al, 1993;DAMIANI et al, 2009;CAPONE et al, 2015;RIBELA et al, 2017). A cadeia de oligossacarídeos pode estar ligada em duas regiões distintas, o que subdivide a glicosilação em Nglicosilação (ligação covalente a uma asparagina determinado pela sequência Asn-X-Ser/Thr, sendo que X não pode ser uma prolina) e O-glicosilação (ligação covalente a uma serina ou treonina (GOOCHEE et al, 1991;PETRESCU et al, 2004;TIAN e ZHANG, 2010).…”
Section: Glicosilaçãounclassified
“…Contudo, existem modificações pós-traducionais realizadas na glicoproteína nativa humana que não ocorrem nas células CHO devido à falta de enzimas especificas. Por exemplo, enzimas que atuam na ligação de resíduos de N-acetilgalactosamina (GalNAc) (N-acetilgalactosamina transferase) ou para sulfatação do resíduo de GalNAc (Sulfatotransferase) (DAMIANI et al, 2009;CAPONE et al, 2015;RIBELA et al, 2017). HOLMEN et al, 1995;SCHENBORN E GOIFFON, 2000;WASHBOURNE e MCALLISTER, 2012;ARAÚJO et al, 2014).…”
Section: Expressão Da Prolactina Humana Em Células De Mamíferosunclassified